The free musical improvisation and the philosophy of Gilles Deleuze (Per Musi, 2012)
Recently, improvisation has been integrated as a theme increasingly present in scholarly environments and it is now considered as an important line of research. Our thinking about free improvisation, besides relying on our practical experience, has the work of French philosopher Gilles Deleuze as a central reference from which we borrow key concepts such as stratification, territory, plan of consistency, molarity and molecularity, body without organs, rhythm, means and refrain. In this article, originally published in Perspectives of New Music, number 49, v.1, we will try to show how these concepts help us think and support the free musical improvisation as we conceive it in our practical and theoretical work.